The Assessment of Students about the School Climate, Coexistence, and Violence in Middle Schools in Northwestern Mexico - Calderón-González, NohemÍ Guadalupe (2022)
Purpose. Identify the assessment of the students about democratic coexistence in their school, the relationship with their classmates, violence on campus, and the school climate in general. Method. It is a quantitative, cross-sectional, and correlational study in which 346 adolescents between 11 and 15 years of age participated; they came from six locations in the state of Sonora, Mexico. The School Climate Scale and the School Coexistence Scale were used, showing evidence of reliability. Comparison of means analysis was performed through Student’s t statistic and logistic regression. Results. There is a significant difference between the two contrasted groups: (a) those who perceive violence and have been molested in the last week at their school, and (b) those who do not perceive violence and have not been molested. The logistic regression model yielded a Nagelkerke R of 0.58, which adequately classifies 82.9% of the cases. Conclusions. This logistic regression model is suitable for predicting the risk of adolescent public high school students of being molested by other peers and perceiving high levels of violence. Therefore, it is recommended to conduct systematic evaluations to identify student profiles and know the relationships between the dimensions of coexistence and school climate.